Influence of Internal Technological Defects on the Mechanical Properties of Structural CFRP (Fracture and Structural Integrity, 2023)
The use of carbon-fiber composite materials (CFRP) in critical cases implies an increase in the resistance to the stability of their mechanical properties. For the purpose of in-depth analysis of defects in the experiments, an integrated approach to mechanical flaw detection and testing of CFRP is used. To determine the parameters of defects in ultrasonic diagnostic sensors and the method of infrared thermography. The main technological defects of structural carbon fiber in samples of the internal "glueline defect", are three geometric shapes (circle, square, rectangle) and a "buckling" inner layer. As a result of flaw detection of individual samples by ultrasonic diagnostics, data were obtained on the shape and size of defects such as "glueline defect" and "buckling". As a result of the study, tensile testing of the samples with and without defects was carried out using the Vic 3D system, the AMSY-6 acoustic emission system, and the FLIR SC7700M thermal imaging system. The tensile strength, elastic modulus, Poisson's ratio, and maximum fracture strains of the studied CFRP without defects and with defects are obtained. The effect of defective zones on the main mechanical parameters is determined. The investigated defects lead to a decrease in strength and elastic characteristics by at least 15% and 5%, respectively.
Keywords: Carbon-fiber composite; Internal technological defects; Tensile; Non-destructive testing; Ultrasonic diagnostics; Infrared thermography; Digital image correlation; Acoustic emission